Temporal trends and determinants of delayed care-seeking after rabies exposure: a 27,930-patient analysis in Tianjin - Shuai Li; Shuangyan Liu (Frontiers in Public Health, 2026)
Objective Prompt care-seeking after rabies exposure is essential for effective post-exposure prophylaxis (PEP). This study aimed to identify independent factors associated with care-seeking delay and to map the full PEP pathway. Methods We retrospectively enrolled 27,930 patients attending the rabies PEP clinic at Santan Hospital, Tianjin, between February 2022 and January 2026. Delay was defined as >12 h from exposure to registration. Multivariable logistic regression, combined with XGBoost and SHAP, identified independent factors for delay and quantified their relative importance. Restricted cubic splines examined the non-linear relationship between age and delay. Subgroup analysis assessed the stability of the association of grade III exposure with more prompt care-seeking. A Sankey diagram traced the PEP pathway. Results The delay rate was 29.7%. Eight independent factors were identified. Adults had a 34% higher risk of delay than children (aOR = 1.34, 95% CI: 1.22–1.47, P < 0.001). Grade III exposure was associated with more prompt care-seeking (aOR = 0.69, 95% CI: 0.65–0.73, P < 0.001). Previous rabies vaccination (aOR = 1.17, 95% CI: 1.11–1.23, P < 0.001) and inadequate wound management (aOR = 1.57, 95% CI: 1.31–1.88, P < 0.001) were associated with higher delay risk. Age showed a non-linear relationship with delay risk, with adults at highest risk. The Sankey diagram showed that inadequate wound management was rare in the PEP pathway, and the two-dose booster schedule achieved a much higher completion rate than the standard schedule. Conclusions Our findings suggest that adults may face the highest risk of care-seeking delay, and that improving healthcare access for adults and promoting simplified vaccination schedules may be key to improving PEP quality.